2010
DOI: 10.21273/hortsci.45.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic Acid Application Enhances Drought Stress Tolerance in Bedding Plants

Abstract: Drought stress is a major cause of postproduction decline in bedding plants. The plant hormone abscisic acid (ABA) regulates drought stress responses by mediating stomatal closure, thereby reducing transpirational water loss. Exogenous ABA applications delay wilting and allow plants to survive short periods of severe drought. The effectiveness of the ABA biochemical, s-ABA (ConTegoä; Valent BioSciences Corp., Libertyville, IL), at delaying wilting and extending shelf life during drought stress was evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
68
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 10 publications
11
68
2
Order By: Relevance
“…The exogenous application of ABA or ABA analogs delays drought stress-induced wilting in a variety of bedding and potted plants (Blanchard et al, 2007;Kim and van Iersel, 2008;Monteiro et al, 2001;Sharma et al, 2005Sharma et al, , 2006Waterland et al, 2010). Although ABA applications allow plants to survive temporary periods of drought stress, negative side effects, including leaf necrosis, chlorosis, or abscission, have been observed in some species (Blanchard et al, 2007;Kim and van Iersel, 2008;Waterland et al, 2010). We observed leaf chlorosis on droughtstressed Tagetes patula (marigolds), Pelargonium ·hortorum (seed geraniums), and pansies treated with drench or spray applications of s-ABA.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…The exogenous application of ABA or ABA analogs delays drought stress-induced wilting in a variety of bedding and potted plants (Blanchard et al, 2007;Kim and van Iersel, 2008;Monteiro et al, 2001;Sharma et al, 2005Sharma et al, , 2006Waterland et al, 2010). Although ABA applications allow plants to survive temporary periods of drought stress, negative side effects, including leaf necrosis, chlorosis, or abscission, have been observed in some species (Blanchard et al, 2007;Kim and van Iersel, 2008;Waterland et al, 2010). We observed leaf chlorosis on droughtstressed Tagetes patula (marigolds), Pelargonium ·hortorum (seed geraniums), and pansies treated with drench or spray applications of s-ABA.…”
mentioning
confidence: 99%
“…We observed leaf chlorosis on droughtstressed Tagetes patula (marigolds), Pelargonium ·hortorum (seed geraniums), and pansies treated with drench or spray applications of s-ABA. Leaf chlorosis in pansies was not directly induced by drought treatment, because symptoms were observed in both watered and drought-stressed plants that were treated with s-ABA (Waterland et al, 2010). It is unclear why s-ABA induced leaf chlorosis and senescence in pansies or how this side effect might be prevented.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ornamentals are mainly grown in protected cultivation systems and the environmental conditions during growth such as light (Mortensen and Gislerød, 1999;Fjeld et al, 1994), day and night temperatures (Moe, 1975;Hamrick, 2003), carbon dioxide levels (Dole and Wilkins, 2005) and relative air humidity Pettersen et al, 2007;Fanourakis et al, 2012) are all shown to affect the postharvest shelf life (for review see, Mayak, 1979a, 1979b). Stomatal behavior and water relations are one of the main factors determining the potential postharvest life, especially for cut flowers, but also for some pot and bedding plants ; van Doorn, 1997;Waterland et al, 2010aWaterland et al, , 2010b. Studies have shown that the stomatal behavior in response to conditions of the cultivation environment, such as relative air humidity Fanourakis et al, 2012), light quality , and photoperiod (Mortensen and Gislerød, 1999), will persist also after harvest.…”
Section: Introductionmentioning
confidence: 99%